A Case of Bipolar Affective Disorder Not Otherwise Specified Or Cyclothymia - Adhikari, B R; Sapkota, N; Gautam, R; Basnet, M; Koirala, P; Rajbhandari, N (Health Renaissance, 2016)
The symptoms of mood disorders can be highly variable from person to person, and there are some differences in the present systems of classification to view some of the presentations of Bipolar Disorder Not Otherwise Specified (BPAD-NOS) and cyclothymia. This case highlights one of such presentations. Health Renaissance 2014;12(3): 221-223